Pengaruh Produk Domestik Regional Bruto, Laju Inflasi dan Tingkat Suku Bunga Terhadap Permintaan Kredit pada Bank-Bank Umum di Provinsi Aceh - Hismendi Hismendi (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2015)
This research is intended to analyze the effect of regional gross domestic product (GDP), inflation and interest rates to the total demand for credit. The method of analysis used in this research is Ordinary Least Square (OSL), with a model secondary data sourced from Bank Indonesia (BI), the Central Statistics Agency (BPS) and data sourced from journals of economics, finance and banking. The results of the data analysis showed that the regional gross domestic product (regional GDP) and a significant positive effect on the demand for total loans, at commercial banks in the province of Aceh. For variable rate of inflation results are positive and significant impact on the total demand for loans at commercial banks in the province of Aceh. While the variable interest rates have negatif effect and significant on the demand for total loans at commercial banks in the province of Aceh. To the researchers expect the Government through the Bank Indonesia as the monetary authority should be able to take control measures against the macro economic variables, especially the movement of inflation because it affects the level of demand for credit. Bank Indonesia can make the determination of the benchmark interest rate in order to lower interest rates on commercial banks. A general decline in interest rates will impact the general increase in credit demand.